Diastereoselective Synthesis of Aryl C‐Glycosides from Glycosyl Esters via C−O Bond Homolysis. (10th March 2021) - Wei, Yongliang; Ben‐zvi, Benjamin; Diao, Tianning
Abstract: C ‐aryl glycosyl compounds offer better in vivo stability relative to O ‐ and N ‐glycoside analogues. C ‐aryl glycosides are extensively investigated as drug candidates and applied to chemical biology studies. Previously, C ‐aryl glycosides were derived from lactones, glycals, glycosyl stannanes, and halides, via methods displaying various limitations with respect to the scope, functional‐group compatibility, and practicality. Challenges remain in the synthesis of C ‐aryl nucleosides and 2‐deoxysugars from easily accessible carbohydrate precursors. Herein, we report a cross‐coupling method to prepare C ‐aryl and heteroaryl glycosides, including nucleosides and 2‐deoxysugars, from glycosyl esters and bromoarenes. Activation of the carbohydrate substrates leverages dihydropyridine (DHP) as an activating group followed by decarboxylation to generate a glycosyl radical via C−O bond homolysis. This strategy represents a new means to activate alcohols as a cross‐coupling partner. The convenient preparation of glycosyl esters and their stability exemplifies the potential of this method in medicinal chemistry. Abstract : A method to synthesize C ‐aryl and heteroaryl glycosides from glycosyl esters is reported. The reaction is particularly useful for preparing β‐aryl nucleoside analogues, leveraging the photoredox activation of dihydropyridine and decarboxylation to homolytically cleave C−O bonds and afford glycosyl radicals.